Enhancement of Solubility and Dissolution Rate of Lumefantrine by Pharmaceutical Cocrystals - Ghawate, V. B. (Asian Journal of Pharmaceutics (AJP), 2023)
The solid-state properties of drug compounds, such as solubility and dissolution, can be changed by cocrystallizing the drug with coformers. The purpose of the current effort was to identify potential coformers and then develop, formulate, and assess the lumefantrine cocrystal. Methods: Lumefantrine cocrystals were created using the solvent evaporation process. The crystalline phase’s melting temperature and solubility were established. DSC, IR, and XRPD were used to characterize the putative cocrystal. Evaluations were also conducted on solubility and dissolution rate, two additional medicinal qualities. Results and Discussion: Lumefantrine-adipic acid cocrystals showed a range in solubility and melting points. Adipic acid and the cocrystals were combined in a 1:1 ratio. The infrared research clearly showed that the lumefantrine distinctive bands were changing. A notable variation in the 2θ of the strong peaks and the crystallinity of cocrystals were indicated by the X-ray powder diffraction pattern. Cocrystal’s differential scanning calorimetry spectra revealed changed melting point endotherms. Due to cocrystallization, the cocrystals showed a higher rate of dissolution, as seen by an increase in the extent of dissolution. Conclusion: The lumefantrine cocrystal with modified properties was prepared with adipic acid having greater solubility and dissolution rate of the drug.